China's quest for economic dominance and energy consumption: Can Asian economies provide natural resources for the success of One Belt One Road?. (9th November 2020) - Bashir, Muhammad Farhan; MA, Benjiang; Shahzad, Luqman; Liu, Biao; Ruan, Qiangjia
Abstract : This research extends the research into foreign direct investments (FDIs) from emerging economies by integrating locational advantage perspective and institution‐based view to empirically analyze the interactive effect of resource endowment in a host economy and how institutional regulations impact on location choice of investors from emerging economies. Our analysis is based on Chinese outward FDI in 36 Asian and Oceanian economies. Empirical findings indicate that resource endowment is contingent upon regulatory institutions from both home and host country settings. Whereas the political risk bears positive influence over FDI and resource endowment, institutional distance and economic freedom have negative impact, which indicates that resource endowment is more appealing to investments from Chinese firms when institutional distance and economic freedom are low and political risk is high.